A ordenação de documentos na Biblioteconomia escolar - Matheus Aguiar de Carvalho (2020)
The shelf arrangement is an activity of information organization, composing the set of documentary mediation processes, whose goal is to propose communication channels that promotes the access and use of documents from a collection by a public. The specificity of the activity lies in the proposition of a logical order to documents of the collection, related with the institution's purposes, and in responses to the information needs of the public. The shelf arrangement has three functions: to promote ways of reading the collection through navigation at the space where the documents are disposed, to constitute the location of the items from a collection, and to serve as an instrument for collection management. Regarding the school libraries specificities, these institutions are approach by the purpose of promoting the information appropriation by the public of base education, through actions that enables them the autonomy to construct meanings from the qualified access and use of documents. The aim of the research is to analyze the development of discussions about shelf arrangement from the perspective of School librarianship through mediation work carried out from school libraries. It is assumed that the shelf arrangement performed in face of the school libraries purposes is insufficient, leading it to the marginalization in mediation work performed by librarians at theses systems. For the investigation, two bibliographic reviews were carried out, the first of narrative character, and the second of integrative character, respectively, of qualitative aspect, and of quantitative and qualitative aspects, in order to constitute a descriptive research regarding the analysis of the proposed themes. After the Introduction, in the second and third section, it is discussed: the documentary mediation as the kind of work performed by the field that is structured in processes based in technical knowledge; and the function of school library approached on infoeducation discussions, developed within USP's research group, ColaborI, which links information and education as two sides that qualifies the librarian work. The fourth section has focused on the shelf arrangement, approaching its conceptual and functional aspects, also its theoretical-methodological, relates to the methods, instruments and methodologies for the constitution of the process. Finally, is discussed the relations between the shelf arrangement and the spatialization and signaling strategies developed in the school library space. The fifth section is about the shelf arrangement in School librarianship, looking at the bibliographic production from this context for highlight the questions related to the development of process, regarding the specificities of the school libraries and of the mediation work performed at its spaces. This is an integrative bibliographic review perform by combining terms representative of the School librarianship, and by terms that accounted for the shelf arrangement, in searches in the BRAPCI, Proquest, DOAJ, INFOBILA, Dialnet e LIBES databases, resulting in 129 publications for analysis. As results found, the shelf arrangement process is widely approached in a fragmented way, which is verified in the denominations used, in the understandings about its functions, in the ways of conceiving the process by the classificatory method as the basis for constituting the call number, and, in spite of these approaches, the questions related to the spatial constitution of the library are posed in a more complete way, considering the relevance of space in offering meanings to subjects about the image and uses of the school library. Finally, it is considered necessary to recover from School librarianship the value of information organization processes for school libraries, which is related to the need to consider the totality of these institutions in terms of mediation processes that allow their qualified performance at school as a library.